Diversity of effects of factors associated with learning in mathematics in Mexican elementary schools - Vargas Sánchez, Juan Roberto; Santillán Hernández, Alma Sofía (IE Revista de Investigación Educativa de la REDIECH, 2022)
The effects of some factors associated with school achievement in the different educational modalities of Mexican elementary education are estimated in this paper. Quantile regression models are estimated using the scores of a national standardized Mathematics test. The results show that the effects are heterogeneous across different modalities and among the various segments of the distributions of the scores of each modality. At the aggregate level, the variable speaking an indigenous language is negatively associated with school performance and the variable family capital positively, the association between the variables is larger in the upper part of the distribution. However, by subsystem, in the indigenous educational modality, speaking an indigenous language has no significant effect on school performance. In contrast, family capital does not affect students’ results in community schools. The findings suggest that the design of educational policy should consider the diversity of contexts and characteristics of students in each subsystem.